2013
DOI: 10.1007/s11883-012-0301-9
|View full text |Cite
|
Sign up to set email alerts
|

Do the Frequencies of Adverse Events Increase, Decrease, or Stay the Same with Long-Term Use of Statins?

Abstract: Statins are widely used for their cholesterol-lowering properties and proven reduction of cardiovascular disease risk. Many patients take statins as long-term treatment for a variety of conditions without a clear-cut understanding of how treatment duration affects the frequency of adverse effects. We aimed to evaluate whether the frequencies of documented adverse events increase, decrease, or remain unchanged with long-term statin use. We reviewed the established literature to define the currently known advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…A number of potential mechanisms underlying the muscular effects of statins have been proposed, the most likely being inhibition of the synthetic pathway causing impaired intracellular function (22). A review that examined whether adverse effects of statins depended on duration of use found that many patients who develop adverse effects do so in early stages of therapy, and the frequency of adverse effects when expressed as a percentage of current users decreases over time (24). This is in line with the current findings that ORs for poor physical functioning were higher for women with low cumulative volumes (Ͻ120 DDD) than for women with high cumulative volumes (Ն365 DDD).…”
Section: Peeters Et Alsupporting
confidence: 84%
“…A number of potential mechanisms underlying the muscular effects of statins have been proposed, the most likely being inhibition of the synthetic pathway causing impaired intracellular function (22). A review that examined whether adverse effects of statins depended on duration of use found that many patients who develop adverse effects do so in early stages of therapy, and the frequency of adverse effects when expressed as a percentage of current users decreases over time (24). This is in line with the current findings that ORs for poor physical functioning were higher for women with low cumulative volumes (Ͻ120 DDD) than for women with high cumulative volumes (Ն365 DDD).…”
Section: Peeters Et Alsupporting
confidence: 84%
“…Namun terapi obat tersebut ternyata memiliki efek samping berupa gangguan gastrointestinal dan dapat menghambat koenzim Q10 yang berfungsi untuk mencegah oksidasi LDL (Marques et al, 2015). Penggunaan statin jangka panjang juga dapat menyebabkan miopati dan toksisitas hati (Ahmad, 2014;Huddy, Dhesi, & Thompson, 2013). Di sisi lain terapi diet dengan cara memodifikasi pola diet menjadi diet rendah lemak jenuh dan kolesterol dapat menurunkan kadar kolesterol total secara lebih murah dan aman untuk dilakukan, namun demikian banyak orang yang mengalami kegagalan dalam menjaga pola diet agar tetap seimbang sehingga perlu adanya inovasi baru tentang solusi terhadap pencegahan peningkatan kolesterol total darah.…”
Section: Pendahuluanunclassified
“…Use of multiple measures of cognition may increase the risk of such normal variation being misinterpreted as effects of medication. Huddy, Dhesi, and Thompson () noted that statin clinical trials are generally shorter than 5 years, rendering it impossible to examine long‐term side effects. Of the randomised clinical trials conducted, only one was conducted over a 42‐month period (Trompet et al., ; Table ).…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%